Optimalisasi Pengajaran Metode Sorogan Dalam Meningkatkan Kemampuan Santri Membaca Kitab Kuning - Satira, Ulfa; Badarasussyamsi, Badarasussyamsi; Huda, Syamsul (Center for Religious Studies and Social Empowerment Foundation, 2023)
This article discusses the implementation of the sorogan method in increasing understanding of the yellow book at the Tanjung Pasir Al-Awwabien Jambi Islamic Boarding School. This article comes from research with a descriptive qualitative approach using ethnographic methods. Data was obtained through observation, interviews and documentation, then analyzed using the Miles and Huberman model and data triangulation. The research results show that the sorogan method allows independent learning and direct guidance from the teacher. The obstacles encountered ranged from a lack of teachers, long hours, student boredom, tardiness, and difficulty reading the yellow book. To overcome this obstacle, it is necessary to add additional yellow book teachers, increase learning variety, and motivate students. Artikel ini membahas pelaksanaan metode sorogan dalam meningkatkan pemahaman kitab kuning di Pondok Pesantren Tanjung Pasir Al-Awwabien Jambi. Artikel ini berasal dari penelitian dengan pendekatan kualitatif deskriptif dengan metode etnografi. Data diperoleh melalui observasi, wawancara, dan dokumentasi, lalu dianalisis dengan model Miles dan Huberman serta triangulasi data. Hasil penelitian menunjukkan bahwa metode sorogan memungkinkan pembelajaran mandiri dan bimbingan langsung dari pengajar. Kendala yang ditemui berkisar pada kurangnya pengajar, waktu yang panjang, kebosanan santri, keterlambatan, dan kesulitan membaca kitab kuning. Untuk mengatasi kendala ini maka diperlukan penambahan pengajar kitab kuning, peningkatan variasi pembelajaran, dan motivasi santri.